The changing scenario of hepatocellular carcinoma in Italy: an update. (2nd December 2020) - Garuti, Francesca; Neri, Andrea; Avanzato, Francesca; Gramenzi, Annagiulia; Rampoldi, Davide; Rucci, Paola; Farinati, Fabio; Giannini, Edoardo G.; Piscaglia, Fabio; Rapaccini, Gian Ludovico; Di Marco, Maria; Caturelli, Eugenio; et al.
Abstract: Background and aims: Epidemiology of hepatocellular carcinoma (HCC) is changing in most areas of the world. This study aimed at updating the changing scenario of aetiology, clinical presentation, management and prognosis of HCC in Italy during the last 15 years. Methods: Retrospective analysis of the Italian Liver Cancer (ITA.LI.CA) database included 6034 HCC patients managed in 23 centres from 2004 to 2018. Patients were divided into three groups according to the date of cancer diagnosis (2004‐2008, 2009‐2013 and 2014‐2018). Results: The main results were: (i) a progressive patient ageing; (ii) a progressive increase of non‐viral cases and, particularly, of 'metabolic' and 'metabolic + alcohol' HCCs; (iii) a slightly decline of cases diagnosed under surveillance, but with an incremental use of the semiannual schedule; (iv) a favourable cancer stage migration; (v) an increased use of radiofrequency ablation to the detriment of percutaneous ethanol injection; (vi) improved outcomes of ablative and transarterial treatments; (vii) an improved overall survival (adjusted for the lead time in surveyed patients) in the last calendar period, particularly in viral patients; (viii) a large gap between the number of potential candidates (according to oncologic criteria and age) to liver transplant and that of transplanted patients. Conclusions: During the last 15 years several aspects of HCC scenario have changed, as well as its management. The improvement in patient survival observed in the last period was likely because of a larger use of thermal ablation with respect to the less effective alcohol injection and to an improved management of intermediate stage patients.